2000
DOI: 10.1046/j.1540-8175.2000.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ventricular Septal Defect Repair Using Intraoperative Transesophageal Echocardiography: Frequency and Significance of Residual Defects in Infants and Children

Abstract: Intraoperative transesophageal echocardiography (IOTEE) is commonly used to assess for residual defect and the need to return to bypass after repair of ventricular septal defect (VSD). The frequency and significance of residual septal defects as noted on IOTEE has not been well defined. We evaluated the frequency of residual VSD via IOTEE and the relationship between size of a residual VSD and rate of reoperation. In addition, we looked at the relationship between the presence of a residual VSD via IOTEE and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 5 publications
2
31
0
1
Order By: Relevance
“…This is comparable to the rates observed after VSD closure for isolated simple VSD in 2 other studies with large sample volumes, namely 25 and 33% in the reports by Dodge-Khatami et al [23] and Yang et al [24], respectively. Our incidence of 12% at predischarge was far more favorable than the incidences of 35 and 34% in those reports, and our 0% incidences at Qp/Qs ratio of the pulmonary blood flow to the systemic blood flow, Pp/Ps ratio of the pulmonary pressure to the systemic pressure, pV PA peak velocity of PA flow, pV ratio ratio of pV PA to pV LVOT follow-up also compared favorably with the 9% incidence at the median follow-up of 3.1 years in the former report by Dodge-Khatami et al…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is comparable to the rates observed after VSD closure for isolated simple VSD in 2 other studies with large sample volumes, namely 25 and 33% in the reports by Dodge-Khatami et al [23] and Yang et al [24], respectively. Our incidence of 12% at predischarge was far more favorable than the incidences of 35 and 34% in those reports, and our 0% incidences at Qp/Qs ratio of the pulmonary blood flow to the systemic blood flow, Pp/Ps ratio of the pulmonary pressure to the systemic pressure, pV PA peak velocity of PA flow, pV ratio ratio of pV PA to pV LVOT follow-up also compared favorably with the 9% incidence at the median follow-up of 3.1 years in the former report by Dodge-Khatami et al…”
Section: Discussionsupporting
confidence: 82%
“…Yang et al concluded that defects on CDI measuring more than 4 mm in diameter predicted the need for immediate reoperation, while 3 mm defects were potentially significant and required additional intraoperative hemodynamic evaluation [24]. Though our measurements of the sizes of the jets were inexact, our method of grading the leakage based on subjective judgment by anesthesiologists experienced with TEE was certainly stricter than the actual measurements in the other two reports.…”
Section: Discussionmentioning
confidence: 76%
“…This phenomenon has been investigated predominantly following corrective cardiac surgery for congenital heart disease, where the incidence of echocardiographically diagnosed residual shunt may be in the range of 33-38 % for certain lesions [1][2][3][4]. However, the accuracy of shunt identification may vary according to the timing of imaging (relative to surgery), and the echocardiographic modality used [3].…”
Section: Introductionmentioning
confidence: 99%
“…In general, a residual defect measuring less than 3 mm at its greatest diameter will not require surgical reintervention, whereas defects greater than 4 mm will require immediate reoperation. In borderline cases or in very small infants, intraoperative hemodynamic assessment of the residual shunt -by measuring the ratio of pulmonary blood flow to systemic blood flow (Qp:Qs) via oxygen saturation measurements -can help in the decision-making process [25].…”
Section: Imaging Of the Adultmentioning
confidence: 99%
“…Residual ASDs are unusual but can occur. Small residual VSDs are common [25,30]. Color Doppler is a very sensitive technique to assess for residual shunts.…”
Section: Follow-up Assessmentmentioning
confidence: 99%